Marriage Counseling and Prospective Mothers Attitudes toward Mental Health - Padauleng, Andi Tenri; Kurniati, Yessy (Universitas Islam Negeri Alauddin Makassar, 2025)
Mental health is a crucial aspect of marriage and pregnancy that is often overlooked in premarital counseling. This study aims to examine the role of marriage counseling in shaping prospective mothers' positive attitudes towards mental health. Through a literature review of ten relevant research articles, it was found that premarital counseling is effective in enhancing mental readiness, reducing anxiety, and fostering prospective mothers' understanding of mental health, marital communication, and preparation for pregnancy. Counseling interventions, whether face-to-face, online, or through technology-based approaches, have been proven to strengthen prospective mothers' readiness for marriage and parenthood. However, long-term effectiveness depends on participants' active involvement and environmental support. Therefore, innovative, interactive, and sustainable counseling programs are necessary to maximize their impact.